From Pituitary Stem Cell Differentiation to Regenerative Medicine - Camilletti, Maria Andrea; Martinez Mayer, Julian; Vishnopolska, Sebastian A.; Perez-Millan, Maria Ines (Frontiers in Endocrinology, 2021)
The anterior pituitary gland is comprised of specialized cell-types that produce and secrete polypeptide hormones in response to hypothalamic input and feedback from target organs. These specialized cells arise during embryonic development, from stem cells that express SOX2 and the pituitary transcription factor PROP1, which is necessary to establish the stem cell pool and promote an epithelial to mesenchymal-like transition, releasing progenitors from the niche. Human and mouse embryonic stem cells can differentiate into all major hormone-producing cell types of the anterior lobe in a highly plastic and dynamic manner. More recently human induced pluripotent stem cells (iPSCs) emerged as a viable alternative due to their plasticity and high proliferative capacity. This mini-review gives an overview of the major advances that have been achieved to develop protocols to generate pituitary hormone-producing cell types from stem cells and how these mechanisms are regulated. We also discuss their application in pituitary diseases, such as pituitary hormone deficiencies.